INSPIRASI WIRAUSAHA ALUMNI: STUDI KUNJUNGAN LAPANGAN KE USAHA CIRENG SAMBAL RUJAK - Puja Trisena; Mustofa Mahfud Fauzi; Abdullah Najib Azzamani (Taksasila Edukasi Insani, 2025)
This community service activity examines the Cireng Sambal Rujak business model pioneered by alumni of the Muhammadiyah University of Jakarta as an inspiration for campus entrepreneurship. This business emphasizes the uniqueness of the product and effective marketing strategy through the Business to Consumer (B2C) model, with direct distribution to consumers via social media, a pre-order system, and collaboration with coffee shops and supermarkets. Data was obtained through observation and interviews on April 16, 2025. The results of the visit showed that despite facing challenges such as product returns due to storage errors, the business owner overcame them by educating partners and strengthening quality control. Financial analysis using the Break Even Point (BEP) approach showed that the break-even point was achieved with sales of at least four products. These findings emphasize the importance of marketing strategies, basic financial management, and product innovation in building a sustainable business. This study also shows the role of alumni in supporting the formation of an entrepreneurial ecosystem in the university environment.Keywords: Entrepreneurship, B2C, Cireng Sambal Rujak, Marketing Strategy, Break Even Point